Status Hukum Relawan Perang Yang Direkrut Ukraina Dalam Perang Rusia-Ukraina - Ilyas Roneo; Sefriani (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
During the war against Russia, Ukraine used military volunteers to help its armed forces defend their territory. There are no regulations governing the status of military volunteers and the legal consequences arising from the use of military volunteers. This research aims to determine the legal status of people involved in war and the legal consequences of granting status to war volunteers. By using normative legal research using a law approach, study case and conseptual. The results of the research show that people involved in the Russian-Ukrainian war are divided into two, namely combatants and war. The legal consequence of granting war volunteer status is that they have the same qualifications as a legitimate combatant and do not receive status as an illegal combatant so they have the rights of being a prisoner of war and can become an object of war.